Problem-Based Learning: Enhancing Grade III Writing Skills in Experimental Reports: Pengaruh Pembelajaran Berbasis Masalah terhadap Kemampuan Menulis pada Siswa Kelas III: Meningkatkan Laporan Eksperimen tentang Sifat Benda Gas - Darin Rahmawati; Vevy Liansari (Academia Open, 2023)
This quantitative pre-experimental study aimed to investigate the influence of the problem-based learning (PBL) model on the writing skills of grade III students in crafting experimental reports on the nature of gas objects. The one-group pretest-posttest design was employed, with a sample of 23 students. The research instrument utilized a description question test. Statistical analysis revealed that the sig value (2-tailed) (0.00) < 0.05, indicating the acceptance of the alternative hypothesis (Ha) and rejection of the null hypothesis (Ho). Hence, it can be concluded that the implementation of the problem-based learning model significantly impacted the students' ability to produce high-quality experimental reports on the nature of gas objects. These findings highlight the potential of PBL as a valuable instructional approach to foster effective writing skills and scientific understanding in young learners. Highlights: Significance of PBL: The study examines the impact of problem-based learning (PBL) on the writing skills of grade III students in the context of crafting experimental reports on the nature of gas objects. Quantitative research approach: A pre-experimental design utilizing the one-group pretest-posttest method was employed to investigate the influence of PBL on the students' writing abilities. Positive outcomes: The results indicate a significant influence of the PBL learning model on enhancing the students' writing skills in the production of experimental reports, emphasizing the potential of PBL as an effective instructional approach for scientific writing in young learners. Keywords: Problem-based learning, Writing skills, Experimental reports, Grade III students, Nature of gas objects.